1999
DOI: 10.1046/j.1440-1681.1999.03124.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Blocking Effects of Tetrodotoxin on Double‐peaked Vasoconstrictor Responses to Periarterial Nerve Stimulation in Canine Isolated, Perfused Splenic Artery

Abstract: 1. In the present study, we investigated the effects of progressive inhibition of neuronal sodium channels by increasing concentrations of tetrodotoxin (TTX; 1-30 nmol/L) on the double-peaked vasoconstrictor responses to electrical periarterial nerve stimulation in the canine isolated and perfused splenic artery. 2. Double-peaked vasoconstrictions (biphasic vasoconstrictor responses) were consistently observed in following electrical stimulation with 30 s trains of pulses at 1-10 Hz. At low frequencies of stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
0
12
1
Order By: Relevance
“…Studies on canine splenic artery also showed that the proportion of ATP and noradrenaline released from sympathetic nerve terminals is dependent upon the stimulation frequency 2,4 , 5,7 . It was therefore claimed that ATP and noradrenaline are possibly released from two separate populations of exocytotic vesicles within the periarterial sympathetic nerve in the canine splenic artery 19–22 . This is also likely to be the case in the canine gastroepiploic artery, because frequency dependent release of ATP and noradrenaline was also demonstrated.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Studies on canine splenic artery also showed that the proportion of ATP and noradrenaline released from sympathetic nerve terminals is dependent upon the stimulation frequency 2,4 , 5,7 . It was therefore claimed that ATP and noradrenaline are possibly released from two separate populations of exocytotic vesicles within the periarterial sympathetic nerve in the canine splenic artery 19–22 . This is also likely to be the case in the canine gastroepiploic artery, because frequency dependent release of ATP and noradrenaline was also demonstrated.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, studies performed in the canine splenic artery showed that guanethidine, an adrenergic neuron blocker, exerted a dominant inhibitory effect on adrenergic rather than purinergic components of sympathetic nerve cotransmission, indicating that guanethidine‐sensitive mechanisms may contribute mainly to determine noradrenaline secretion from neurosecretory vesicles rather than ATP secretion 19 . In addition, progressive inhibition of sodium channels by increasing the concentration of tetrodotoxin exerted a more preferential inhibition of adrenergic rather than purinergic components, suggesting that tetrodotoxin‐sensitive sodium channels may have a more important role in determining the adrenergic rather than purinergic transmission of sympathetic nerves 20 . It was further suggested that prolonged cold storage, which causes irreversible degeneration of adrenergic nerve fibres, preferentially depresses cotransmission of the purinergic component, whereas the adrenergic component is largely unaffected 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Yang & Chiba (1999b,1999c) observed that the function of adrenergic component largely remained even in the cold stored preparation for 4–7 days but purinergic component of response to nerve stimulation was markedly damaged, because the first peaked responses became clearly smaller but second ones were only slightly depressed. Moreover, Yang & Chiba (1999d) also demonstrated that a smaller dose of tetrodotoxin, a selective sodium channel blocker inhibited only an adrenergic component but not purinergic component, showing that tetrodotoxin blocks second peaked vasoconstrictions induced by periarterial nerve stimulation in canine splenic artery but not first peaked ones. More recently, Yang & Chiba (1999e) demonstrated that guanethidine preferentially inhibited the second peaked adrenergic but not the first peaked purinergic responses.…”
Section: Discussionmentioning
confidence: 99%
“…In the rabbit ileocolic artery, activation of presynaptic α 2 -adrenoceptors preferentially inhibits the release of noradrenaline [16]. In canine splenic arteries, adrenergic neuron blockade with guanethidine [189] or inhibition of sodium channels by tetrodotoxin [188] mainly depresses the adrenergic rather than the purinergic component. Opposing to this, the purinergic component is depressed, rather than the adrenergic component, after irreversible degeneration of adrenergic nerve fibres due to cold storage [190] or with dipyridamole [119].…”
Section: Effects Mediated By P2x and P2y Receptors In The Splanchnic mentioning
confidence: 99%